Building Lenggong World Heritage site brand identity: Assessing core values of local community - Md Noor, Shuhaida; Khor , Yoke Lim; Mohamed, Ramli (2013)
This paper looks into the preliminary but yet critical step in developing a strong brand for the Lenggong Valley World Heritage site, that is the development of the site’s brand identity. The Lenggong Valley has recently been listed as UNESCO’s world heritage site. At this nascent stage, it is critical that the brand identity of the site is identified to ensure consistency and effectiveness of future promotion and marketing efforts. Brand identity in this study refers to the brand elements considered important by the stakeholders to be projected to the target audience. It represents the stakeholders’ promise to the audience. As established in the literature, in developing tourism destination brand identity, it is important that the aspirations and cultural values of the brand owner (e.g. local residents, state and central Governments) is established at an early stage so that the development of tourism destinations will be pegged to their aspirations and values rather than external and alien values. The agreement of the stakeholders on the brand identiy is very important not only to ensure a consistent and integrated brand identity will be projected to tourists, but also to assure that they will support and work together for the sustainability of the Lenggong Valley WHS. This research assesses the core values and aspirations of one of the key stakeholders of the Lenggong Valley World Heritage Site that is the local community. Twenty local community representatives, including the head of village and the head of an indigenous tribe, and local residents were interviewed to gain insights on what they consider to be key values to be encapsulated as the identity of the Lenggong Valley World Heritage Site. The findings revealed that the local community’s values do not coincide with the values that were promoted in getting the valley enlisted as the World Heritage Site. The heritage that is highly valued by the local community encompasses non-archaeological heritage.